ANALYSIS OF FOOD AND BEVERAGE SANITATION HYGIENE THROUGH STANDARD OPERATIONAL PROCEDURE AS AN EFFORTS TO PREVENT FOOD CONTAMINATION (CASE STUDY AT MELTING POT CAFE, CONCORDE HOTEL KUALA LUMPUR): ANALYSIS OF FOOD AND BEVERAGE SANITATION HYGIENE THROUGH STANDARD OPERATIONAL PROCEDURE AS AN EFFORTS TO PREVENT FOOD CONTAMINATION (CASE STUDY AT MELTING POT CAFE, CONCORDE HOTEL KUALA LUMPUR) - Srinugroho, Thomas Mario; Anggraini, Dhita Paramita; Puspitasari, Reny; 'Ulya, Ayu Fitriatul (Jurnal Pariwisata Tourista, 2025)
Sanitary hygiene in the food processing process is one of, if not the most important aspect in preventing food contamination. Therefore, to prevent unwanted food contamination, hotels use Standard Operational Procedure as a daily operational guideline. Standard Operational Procedure is a guide used to ensure that the operational activities of an organization and/or company run smoothly. Therefore, sanitation hygiene and food contamination are closely related, with the Standard Operational Procedure as a guideline as well as a means of improving daily operations. This study aims to analyze the level of food and beverage sanitation hygiene to prevent food contamination through the implementation of standard operational procedures at Melting Pot Cafe, Concorde Hotel Kuala Lumpur. The method used in this research is a case study method using a descriptive approach. In this study, data was collected using direct observation techniques and questionnaires given to 30 staff who were directly involved in the food processing process. The results showed that there are several points that need to be improved in terms of food processing, resulting in a Standard Operational Procedure that is expected to improve daily hotel operations.